Penyebab dan Penyelesaian SP2DK Terhadap Pelaporan SPT Tahunan Orang Pribadi Studi Kasus Terhadap Klien KKP XYZ - Zidane, Enrico Muhammad; Widajantie, Tituk Diah (Masyarakat Ekonomi Syariah Bogor, 2024)
The aim from this research is to find out the main factor causing the publication of SP2DK and how to complete it. The researcher decided to use a qualitative research method with a qualitative descriptive approach. This research is a case study of clients from KKP XYZ. Data was collected through observation techniques and through documents from a second party, namely KKP XYZ. The type of data analysis technique used in this research is qualitative descriptive data analysis technique. The results of the research concluded that the main factor in the issuance of SP2DK was due to a misunderstanding of the concept of reporting and filling out the Annual tax return between the KKP and the KPP, then to resolve this, the Taxpayer had to provide a response and reply to the DJP and make a revised Annual SPT to respond to the SP2DK and so that no investigation was carried out.